Memotivasi Guru Dalam Meningkatkan Kinerja Mengajar di SMP Negeri 2 Siak Hulu - Agusman, Agusman (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Motivation of a teacher is very supportive in efforts to improve student achievement and improve the quality of education of a school. Because if the teacher's motivation is low then the quality and quantity of education within a school organization is very difficult to be realized let alone to be improved. The facts in SMP N 2 Siak Hulu found the phenomenon of some teachers are less motivated in teaching students in school so that teachers are less passionate and less enthusiastic in teaching. Using school action research and analyzed by qualitative techniques obtained results provide motivation to teachers in teaching can improve teacher performance. Keywords: Teacher motivation, teacher performance